FBXL19 recruits CDK-Mediator to CpG islands of developmental genes priming them for activation during lineage commitment - Dimitrova, E; Kondo, T; Feldmann, A; Nakayama, M; Koseki, Y; Konietzny, R; Kessler, B; Koseki, H; Klose, R (eLife Sciences, 2018)
CpG islands are gene regulatory elements associated with the majority of mammalian promoters, yet how they regulate gene expression remains poorly understood. Here, we identify FBXL19 as a CpG island-binding protein in mouse embryonic stem (ES) cells and show that it associates with the CDK-Mediator complex. We discover that FBXL19 recruits CDK-Mediator to CpG island-associated promoters of non-transcribed developmental genes to prime these genes for activation during cell lineage commitment. We further show that recognition of CpG islands by FBXL19 is essential for mouse development. Together this reveals a new CpG island-centric mechanism for CDK-Mediator recruitment to developmental gene promoters in ES cells and a requirement for CDK-Mediator in priming these developmental genes for activation during cell lineage commitment.